2017
DOI: 10.23943/princeton/9780691178264.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Unquiet Frontier

Abstract: From the Baltic to the South China Sea, newly assertive authoritarian states sense an opportunity to resurrect old empires or build new ones at America's expense. Hoping that U.S. decline is real, nations such as Russia, Iran, and China are testing Washington's resolve by targeting vulnerable allies at the frontiers of American power. This book explains why the United States needs a new grand strategy that uses strong frontier alliance networks to raise the costs of military aggression in the new century. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some hyperchaotic behavior in SHG with pump of pulses has been shown [111]. The two largest Lyapunov exponents versus a duration of pulse T 1 are presented in Fig.…”
Section: F Pulsed External Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Some hyperchaotic behavior in SHG with pump of pulses has been shown [111]. The two largest Lyapunov exponents versus a duration of pulse T 1 are presented in Fig.…”
Section: F Pulsed External Fieldmentioning
confidence: 99%
“…Alekseeva et al [109] presented a detailed study of the spatial evolution of multifrequency fundamental and second-harmonic radiation and showed that the system may exhibit a spatial chaos due to multiple competing processes. Also, a hyperchaotic dynamic in SHG was numerically predicted [110,111].…”
Section: A Introductionmentioning
confidence: 99%